PENGARUH DEBT TO EQUIY RATIO (DER), RETURN ON EQUITY (ROE) DAN TOTAL ASSET TURNOVER (TATO) TERHADAP NILAI PERUSAHAAN DENGAN HARGA SAHAM SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERTAMBANGAN DI BURSA EFEK INDONESIA PERIODE 2022-2024 - Mila Aysah; Ida Subaida; Ardhya Yudistira Adi Nanggala (Jurnal Mahasiswa Entrepreneurship (JME), 2026)
This study aims to determine the effect of Debt to Equity Ratio (DER), Return on Equity (ROE), and Total Asset Turnover (TATO) on Company Value through Stock Price as an Intervening Variable in Mining Companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024. This study uses a quantitative method with a descriptive approach. The sampling technique used is purposive sampling. The data used are secondary data in the form of financial statements and company annual reports obtained from the official website of the Indonesia Stock Exchange (IDX). Data analysis was carried out using the Structural Equation Modeling (SEM) method with the help of SmartPLS 3.0 software. The results show that Debt to Equity Ratio (DER) has a negative and significant effect on Stock Price, while Return on Equity (ROE) has a positive but insignificant effect on Stock Price. Total Asset Turnover (TATO) has a negative but insignificant effect on Stock Price. Meanwhile, Debt to Equity Ratio (DER) and Return on Equity (ROE) have a positive but insignificant effect on firm value, while Total Asset Turnover (TATO) has a positive and significant effect on firm value. Stock price also has a positive and significant effect on firm value. The results of indirect hypothesis testing indicate that Debt to Equity Ratio (DER) has a negative and significant effect on firm value through stock price, while Return on Equity (ROE) and Total Asset Turnover (TATO) have a positive and negative but insignificant effect on firm value through stock price.